Mathematics Model Interest and Actual Use of The ABC Digital Wallet - Minto Waluo; Mega Cattleya PA Islami; Yekti Condro Winursito; M. Rachman Wayulo; Annisa Marwadelia (Nusantara Science and Technology Proceedings, 2023)
The emergence of the COVID-19 pandemic had an impact on all business sectors, both goods and services, one of which is the electronic money sector which is related to increasing transaction values. The increase in transactions using non-cash money has resulted in high competition between providers of similar products. Seeing this phenomenon, Dompet Digital XYZ as a digital wallet service provider who is in the second position needs tips to be able to shift Gojek to its competitor who is in the first position. The purpose of this research is to find out how the variables of perceived benefits, ease of use, and security affect the actual interest and use and determine the right strategy for the ABC digital wallet service. Data collection was carried out by distributing questionnaires to 135 respondents aged 18 years who had used the XYZ digital wallet service at least 1 time. Data processing was carried out using the Structural Equation Modeling (SEM) AMOS 26 method. Based on the results of the analysis, the results of the study where the perceived benefit variable has a positive and significant effect on interest in the use, the variable perception of ease of use cannot be proven, and the perceived security variable has a positive and significant effect on interest in the use, and the variable interest in use has a positive and significant effect on actual use. Based on the analysis results obtained, the mathematical model is obtained as follows: Y2 = 0.264 X1 + 0.388 X3.